Analyses on face stability of shallow tunnel considering different constitutive models - Chunyu, Luo; Zhengpeng, Jia; Zhi, Li; Kefeng, Xiao; Bohan, Wu (Frontiers in Materials, 2023)
Based on the finite element limit analysis method, the stability of the face under three constitutive models, the Mohr-Coulomb model (MC), the modified Cambridge model (MCC) and the Drucker-Prager model (DP), was analyzed. The ultimate support pressure of the face, and the influence of factors such as different burial depth ratios (C/D), cohesion (c) and friction angle (φ) in the MC model are also discussed. The results show that the safety factor obtained by the MCC model under the same support pressure is always smaller than that of the MC model, and the difference is the largest when there is no support pressure. As the support pressure increases, it will gradually approach the MC model. When the support pressure is small, the safety factor obtained by DP model is larger than the MC model, but when the support pressure is large, it is smaller than the MC model, and the final difference tends to be stable. It is necessary to select appropriate constitutive model according to different rock mass in practical engineering. The self-stabilizing performance of the face is not affected by C/D, the ultimate support pressure will increase with the increase of C/D, decrease linearly with the increase of cohesion, and decrease with the increase of friction angle. When the friction angle is small, the ultimate support pressure is greatly affected by C/D, and when the friction angle is large, it is hardly affected by C/D.